The Empowerment of Producing Instant Herbal Medicine Through Institutionalization the Woman Farmer Group” Sekar Sari” in Tulungrejo Ngantang Village, Malang, East Java - Rokhani; Nurul Dwi N; M. Rondhi; Listiani; Pangestu, Angger Dwi; Khoiriyatul Ma’rifah, Annisa (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Strengthening the womanfarmers group institution is important as an effort to ensure the sustainability of the KWT business, especially from an economic perspective, in order to increase the income of women who generally work as daily laborers (local term: mreman). The sustainability of this business is strongly supported by strong social capital, meaning that there is a close link between social capital and business sustainability. This institutional strengthening was carried out through lectures and informal discussions by inviting resource persons from KWT who were more advanced as a source of inspiration for KWT Sekar Sari. Meanwhile, intervention from the marketing side was carried out to expand the market for instant herbal products into 5 variants by utilizing social media networks. The intervention in the form of packaging was carried out as an attraction for consumers considering that packaging is still very simple. The aim of this service activity is; 1) so that KWT Sekar Sari is strong from an institutional perspective so that members who join are active, 2) improve the quality of packaging so that instant herbal medicine products attract consumer interest., 3) improve the skills of KWT members and administrators in photographing products; 4) introduce instant herbal medicine products through digital platforms by utilizing social media to expand the marketing area. The solutions offered to overcome partner problems are: 1) Strengthening the KWT Sekar Sari institution; 2) Expanding the marketing of instant herbal medicine products through social media networks, and 3) Improving the quality of product packaging.